Dynamic layer-by-layer films on nanofiber membrane: a platform for ultra-sensitive bacterial concentration detection. Issue 57 (28th June 2018) - Yu, Zhenguo; Lu, Zhentan; Huang, Yu; Li, Mufang; Wang, Wenwen; Liu, Ke; Wang, Dong
Abstract : A new platform was established for ultra-sensitive bacterial concentration detection within 5 min. Abstract : Herein, a new platform was established for ultra-sensitive bacterial concentration detection. The sensing system had a linear relationship with the logarithm of bacterial concentration from 1 × 10 1 to 1 × 10 5 CFU mL −1 within 5 min. Moreover, the platform showed excellent consistency compared with the traditional standard method against practical samples.